Mr. Inky : spider with an attitude - Hildahl, Esther J. ([Publisher not identified], 2013)
Meet Mr. Inky-- the lovable talking spider with bad grammar and an attitude. He's come to live in Vicki Wyatt's bedroom. She tries to get him to leave, even threatening him with one of her yellow flip-flops. But he refuses to go, telling her that it's "his" home, too. Find out what happens when Vicki decides to take him to school for her science project.